2012
DOI: 10.1002/jobm.201100335
|View full text |Cite
|
Sign up to set email alerts
|

Flagella and bacterial pathogenicity

Abstract: As locomotive organelles, flagella allow bacteria to move toward favorable environments. A flagellum consists of three parts: the basal structure (rotary motor), the hook (universal joint), and the filament (helical propeller). For ages, flagella have been generally regarded as important virulence factors, mainly because of their motility property. However, flagella are getting recognized to play multiple roles with more functions besides motility and chemotaxis. Recent evidence has pinpointed that the bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
234
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(242 citation statements)
references
References 69 publications
4
234
1
3
Order By: Relevance
“…8), all of the flagella-related genes were preferentially expressed during early infection, with high expression 6 hpi. This would support the idea that flagellin might trigger the activation of immune responses in the host to attract macrophages and initiate productive infection (Steiner et al 2000, McCarthy et al 2008, Rojas et al 2009, Duan et al 2013, Rozas & Enriquez 2014.…”
Section: Discussionsupporting
confidence: 67%
“…8), all of the flagella-related genes were preferentially expressed during early infection, with high expression 6 hpi. This would support the idea that flagellin might trigger the activation of immune responses in the host to attract macrophages and initiate productive infection (Steiner et al 2000, McCarthy et al 2008, Rojas et al 2009, Duan et al 2013, Rozas & Enriquez 2014.…”
Section: Discussionsupporting
confidence: 67%
“…Motility and biofilm are two virulence-associated phenotypes relevant to bacterial pathogenicity in vivo (28). Since DksA was shown to be involved in these phenotypes in other pathogen (15), we were interested in characterizing the possible role of DksA in Salmonella motility and biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that flagella are necessary for biofilm formation by E. coli and other bacteria such as Listeria monocytogenes and Yersinia enterocolitica (22,34,35). Furthermore, in addition to the presence of flagellar filaments, motor proteins that cause flagellar rotation are required.…”
Section: Discussionmentioning
confidence: 99%